Invasive Pneumococcal Disease in Latvia in PCV10 Vaccination Era, 2012–2018 - Savrasova, Larisa; Krumina, Angelika; Cupeca, Hedija; Zeltina, Indra; Villerusha, Anita; Grope, Ilze; Viksna, Ludmila; Dimina, Elina; Balasegaram, Sooria (Frontiers in Pediatrics, 2021)
In 2010 in Latvia, invasive pneumococcal disease (IPD) became notifiable for physicians and vaccination of infants with 4 doses of 7–valent pneumococcal conjugate vaccine (PCV7) commenced. In 2012, 10–valent pneumococcal conjugate vaccine (PCV10) (3 doses – at 2,4 and 12-15 month of age) vaccination was introduced. We described incidence and serotype distribution of IPD in Latvia and investigated serotypes associated with death from IPD based on surveillance data. Adult vaccination against pneumococcal infection is not included at the national immunization program. Laboratory confirmed IPD cases are passively notified to the Centre for Disease Prevention and Control of Latvia (CDPC) by laboratories and clinicians. We calculated incidence by age, sex, case fatality and trend in serotypes by conducting a retrospective population-based crossectional study based on national IPD surveillance data. From 2012 to 2018 466 cases of IPD were reported. The highest notified incidence was in 2015 (4.4/100000) fell to 3.9 in 2018. The highest mean annual IPD incidence was in infants (4.8) and in elderly (6.0). PCV10 vaccine serotypes were the most prevalent in IPD cases up to 2015 with a decreasing trend from 50% (20/40) in 2012 to 19% (14/74) in 2018 (chi2 test for trend of odds =0.000). PCV23nonPCV13 vaccine serotypes had an increasing trend and rose from 18% (7/40) to 34% (25/74) (chi2 test for trend of odds = 0.000). Non-vaccine serotypes had an increasing trend and rose from 13% (5/40) to 27% (20/74) (chi2 test for trend of odds = 0.038). Reported total case fatality was 19% (87/466). The highest 36% (20/56) was reported in 2013. After adjusting for age, S.pneumoniae serotype 3 was associated with death from IPD(adjusted OR 2.3 95%CI 1.25-4.12 p 0.007). Surveillance data indicate evidence of serotype replacement with increasing trend of serotype 19A and PPV23nonPCV13 and NonVaccine serotypes. Serotype 3 and age were associated with fatal IPD outcome. Further studies of S.pneumoniae carriage would be useful providing more evidence of characterizing serotypes circulation.